Evaluation of Midwifery Service Standards during the Covid-19 Pandemic - Nurul Azizah (Jurnal MIDPRO, 2022)
During the COVID-19 pandemic, health services became a burden for the community. The number of cases of Covid-19 transmission made people reluctant to come to health facilities. Health workers are encouraged to continue carrying out their roles to adapt and provide optimal service to patients. Likewise, midwives are advised to continue to provide maternal and child health services by complying with health protocols. Based on data reported by the Central IBI in June 2020, 974 of 9,296 PMBs were closed, maternal and child health services were temporarily suspended from PMBs who continued to provide services. Most of them did not offer midwifery services following standard health protocols. This study was conducted to describe the evaluation of midwifery service standards during the COVID-19 pandemic. The research design used a cross-sectional with chi-square statistical test to determine the standard practice of midwifery services during the covid-19 pandemic, which was analyzed descriptively. Sampling with quota sampling, with a total of 30 respondents. The research instrument used a questionnaire. The results of this study indicate that in the implementation of midwifery services according to standard health protocols during the COVID-19 pandemic, most of which were 53% carried out according to pregnancy, 67% of deliveries were not carried out according to health protocols, almost 90% of postpartum & BBL services were carried out accordingly, and 100% of family planning services are carried out according to health protocols. The conclusion is that most midwives carry out standard midwifery services during the covid-19 pandemic